Impact of the functional status of saeRS on in vivo phenotypes of Staphylococcus aureus sarA mutants. Issue 6 (12th May 2014) - Beenken, Karen E.; Mrak, Lara N.; Zielinska, Agnieszka K.; Atwood, Danielle N.; Loughran, Allister J.; Griffin, Linda M.; Matthews, K. Alice; Anthony, Allison M.; Spencer, Horace J.; Skinner, Robert A.; Post, Ginell R.; Lee, Chia Y.; et al.
Summary We investigated the in vivo relevance of the impact of sarA and saeRS on protease production using derivatives of the USA300 strain LAC. The results confirmed that mutation of saeRS or sarA reduces virulence in a bacteremia model to a comparable degree. However, while eliminating protease production restored virulence in the sarA mutant, it had little impact in the saeRS mutant. Additionally, constitutive activation of saeRS (saeRSC) enhanced the virulence of LAC and largely restored virulence in the isogenic sarA mutant. Based on these results, together with our analysis of the representative virulence factors alpha toxin, protein A (Spa), and extracellular nucleases, we propose a model in which the attenuation of saeRS mutants is defined primarily by decreased production of such factors, while constitutive activation of saeRS increases virulence, and reverses the attenuation of sarA mutants, because it results in both increased production and decreased protease‐mediated degradation of these same factors. This regulatory balance was also apparent in a murine model of catheter‐associated infection, with the results suggesting that the impact of saeRS on nuclease production plays an important role during the early stages of these infections that is partially offset by increased protease production in sarA mutants.